Pengembangan Komunikasi Pemasaran UMKM D’Lollypop Melalui Media Sosial dan E-Commerce Selama Pandemi Covid-19 - Gita Putri Azahro; Annisha Ayu Amalikha; Shofia Maidah Ariani; Karens Sabrina Purnasari; M Daffa Firdauzan; Dwi Prasetyo (LPPM Stikosa - AWS, 2021)
The Covid-19 pandemic has had a major impact on many people. Starting from large companies, small companies to micro, small and medium enterprises (UMKM). D'Lollypop My Craft is one of UMKM that affected covid-19. This activitie in the field of creating programs that can provide change in several areas. One of them is in terms of promotion through digital media such as Instagram social media, Tiktok and Shopee E-commerce. With some content including product photos and content video creation to introduce UMKM product's D'Lollypop My Craft. This KKL activity gives a new feel with the presence of Store Banners, X-Banners, catalogs, stickers, and packaging mats. The method used in this study is a descriptive method with a qualitative approach. The results of this study are the development of sales through online media so that it can increase turnover by 75 percent.